Caracterización del extracto del falso Tabaco (nicotiana glauca). - Cando Santo, Natalia Mishel (2022)
The research project has as aim to characterize the false tobacco extract (Nicotiana glauca). Once, it was determined the methodology, was carried out the elaboration plant extract, under study into Bromatology Laboratory from Agroindustrial Engineering Career. It was planned a Completely Randomized Block Design (DBCA) AxBxC, into factorial arrangement (2x2x2), with 8 treatments and two repetitions, by giving a 16 experimental units total. By counting with three factors and with two levels, each one, Factor A (Solvents types), Factor B (Maceration time), Factor C (Plant state), once, it was performed the treatments with their respective repetitions, were measured the parameters. Physicochemical, such as pH and °Brix in a 17 days’ time, once, it was got the measurements, it was proceeded to analyze each day, by entering the data to the InfoStat statistical tool, this allowed to appreciate how interacted the treatments and helped to determine the best treatment, what was t7 (a2b2c1), corresponding to ethanol + 48 hours + fresh leaves. Subsequently, it was carried out a best treatment sensory analysis, which it was assessed the odor, giving an intense odor result, a dark green color and an extract liquid appearance characteristic from a plant source. At the best treatment, it was made a physicochemical analysis, where it was got the following parameters: Total solids 0.92%, ashes 0.01%, pH 5.92, acidity 0.05%, soluble solids 20.25% and density 0, 8467g/ml. Next, it was performed a microbiological analysis, on this treatment, where it was got the following parameters: Total Mesophilic Aerobic Count, Total Coliforms, Molds and Yeasts < 10 CFU/ml. It was also carried out the phytochemical profile determination, at this treatment relapsed into the t7 (a2b2c1), what corresponds to ethanol + 48 hours + fresh leaves, where it was identified secondary metabolites, such as alkaloids, flavonoids and, to a lesser extent, saponins, since a large extent, alkaloids have fungal, antiseptic and antibacterial properties, so nicotine tends to be a toxic alkaloid, what acts on the insect’s mortality. Therefore, it was caried out a false tobacco ethanolic extract bioassay, whose controlled the genus Immigrant fruit fly fruit fly pest, considering an environmentally biodegradable product, and at the same time, being a promising natural source extract into the fruit products application. At the end, it was determined a $3.23 cents cost for the fake tobacco extract into a 450 ml presentation available in the natural products market for organic agriculture.